STUDI KORELASI KEANEKARAGAMAN BURUNG DAN POHON PADA LAHAN AGROFORESTRI BLOK PEMANFAATAN KPHL BATUTEGI - Alviana Indah Saputri; Dian Iswandaru; Christine Wulandari; Samsul Bakri (Jurnal Belantara, 2022)
The existence of birds and trees has an important role in the ecosystem, especially agroforestry. The purpose of this study was to analyze the relationship between bird and tree diversity. Data was collected using plot and point count methods, then analyzed descriptively quantitatively using diversity index, significant value index and correlation analysis. The results showed that the index value of bird and tree diversity was classified into the medium category, namely H'=2.06 and H'=1.02. Correlation analysis shows that there is no significant relationship between the two variables. The absence of a relationship between the two variables occurs due to the lack of availability of bird feed on agroforestry land so that the birds only use trees to play, stop or perch. A more diverse variety of plants can increase bird diversity, but in this study this was not found. Based on the research results, it is hoped that the government and the community will increase bird diversity through increasing tree variety so that the quality of the ecosystem balance is maintained.